Peningkatan Produktivitas Pertanian Era Society 5.0 Pasca Pandemi 2021
DOI: 10.25047/agropross.2021.230
|View full text |Cite
|
Sign up to set email alerts
|

Serangan Hama Utama Pada Tanaman Bawang Merah Yang Diaplikasi Dengan Biostimulan

Abstract: Pertumbuhan bawang merah dipengaruhi oleh kecukupan nutrisinya. Pemberian biostimulan yang terbuat dari ekstrak rumput laut dan bakteri endofit terpilih diharapkan dapat meningkatkan pertumbuhan tanaman dan produksi bawang merah. Selain itu, pengaruh pemberian biostimulan terhadap serangan organisme pengganggu tanaman utama bawang merah (Spodoptera exigua) juga perlu diketahui. Penelitian yang dilaksanakan di Desa Cikole, Lembang, Bandung Barat pada bulan April-Mei tahun 2021 dilakukan untuk mengetahui perkemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…The use of a consortium of endophytic bacteria producing growth regulators enriched by seaweed can be an alternative to synthetic growth regulators, especially to support organic agriculture [44,45]. Previous studies have been conducted using seaweed enriched with endophytic microbes in chili peppers, onions, and shallots in the field [46,47,48]. The results of the study showed that the use of endophytic microbes enriched with seaweed can increase the yield of chili fruit [46], and bio-stimulants can reduce the use of chemical fertilizer on shallot plants [48].…”
Section: Introductionmentioning
confidence: 99%
“…The use of a consortium of endophytic bacteria producing growth regulators enriched by seaweed can be an alternative to synthetic growth regulators, especially to support organic agriculture [44,45]. Previous studies have been conducted using seaweed enriched with endophytic microbes in chili peppers, onions, and shallots in the field [46,47,48]. The results of the study showed that the use of endophytic microbes enriched with seaweed can increase the yield of chili fruit [46], and bio-stimulants can reduce the use of chemical fertilizer on shallot plants [48].…”
Section: Introductionmentioning
confidence: 99%